2021
DOI: 10.3390/cells10020333
|View full text |Cite
|
Sign up to set email alerts
|

TFEB Biology and Agonists at a Glance

Abstract: Autophagy is a critical regulator of cellular survival, differentiation, development, and homeostasis, dysregulation of which is associated with diverse diseases including cancer and neurodegenerative diseases. Transcription factor EB (TFEB), a master transcriptional regulator of autophagy and lysosome, can enhance autophagic and lysosomal biogenesis and function. TFEB has attracted a lot of attention owing to its ability to induce the intracellular clearance of pathogenic factors in a variety of disease model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 96 publications
1
27
0
Order By: Relevance
“…In addition, a recent report indicated that TFE3 overexpression augments autophagy flux and ameliorates ER stress-induced apoptosis in neurons following spinal cord injury ( Zhou et al, 2020 ), supporting the notion that TFE3 activation could be neuroprotective. Efforts have been made to develop TFEB agonists to enhance autophagy in neurodegenerative disease ( Chen et al, 2021 ), and our results suggest that TFE3 could also be a promising drug target.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, a recent report indicated that TFE3 overexpression augments autophagy flux and ameliorates ER stress-induced apoptosis in neurons following spinal cord injury ( Zhou et al, 2020 ), supporting the notion that TFE3 activation could be neuroprotective. Efforts have been made to develop TFEB agonists to enhance autophagy in neurodegenerative disease ( Chen et al, 2021 ), and our results suggest that TFE3 could also be a promising drug target.…”
Section: Discussionmentioning
confidence: 70%
“…This motif, termed coordinated lysosomal expression and regulation (CLEAR) element, consists of an E-box (CANNTG) identified by MIT/TFE family transcription factors (e.g., TFEB and TFE3) 26 . TFEB promotes transcription and expression of its target genes by specifically binding to the distinct CLEAR motif in the target promoter 26 , which increases the biogenesis of lysosomes and improves their degradation ability 27 .…”
Section: New Understanding Of Lysosomal Function and Regulation Recent Findings On Lysosomal Functionmentioning
confidence: 99%
“…The overexpression of TFEB increases the autophagy levels in major organs and protects against LPS induce acute lung injury (Liu et al, 2019) or inflammatory liver injury and pancreatitis (Chao et al, 2018;Wang et al, 2019). Moreover, the pharmacological activation of TFEB by extrinsic stimuli or intrinsic signaling molecules is known to protect against septic liver injury, acute kidney injury (Li D. et al, 2021), and cardiac dysfunction (Unuma et al, 2013).…”
Section: Organ Protectionmentioning
confidence: 99%
“…Although the overexpression of TFEB has been investigated in cells and experimental rodents to evaluate its ability to activate the ALP, the pharmacological modulation of TFEB by means of activators is more desirable for therapeutic applications in the short term. For example, recent research has reported that small molecules and biomacromolecules (e.g., microRNAs (miRNA), polysaccharides and peptides) can modulate the ALP by activating TFEB (Xu H. et al, 2020;Chen et al, 2021). These activators have been categorized according to the pharmacological mechanisms by which they regulate TFEB.…”
Section: The Pharmacological Application Of Tfeb Activators As a Therapeutic Option For Sepsismentioning
confidence: 99%